Historic low stand of Great Salt Lake, Utah: I - Paul W. Jewell (SN Applied Sciences, 2021)
Abstract Great Salt Lake of Utah is among the largest and most ecologically important water bodies in North America. Since the late 1950s, the lake has been divided into two hydrologically distinct water bodies by a rock-fill railroad causeway. Flux through the causeway is driven by two forces: differential surface elevation and differential density between the north and south arms. The south arm features episodic vertical stratification due to the influx of deep, dense brine from the north arm. The source of this brine (a breach, two culverts, or subsurface flow) has been investigated over the past 50 years. Quantification of subsurface water flux through the causeway has been problematic due to the heterogeneous and slowly compacting nature of the causeway fill over time. Between 2008 and 2015, enhanced gauging of various surface inflows and outflows and density measurements made throughout the lake permitted detailed water volume calculations of both lake arms. Results show that during high precipitation years, density-driven, north-to-south flow through the causeway predominates due to freshening of water in the south arm. At other times, south-to-north head gradient driven flow and north-to-south density-driven flow are approximately equal. The model suggests subsurface flux through the causeway is one important driver of the ecologically important deep brine layer in the south arm of the lake over the past 20 years.